The Role of Nurses in Managing Post-Traumatic Stress Disorder (PTSD) - Alayli, Omran Abdullah Mohammed; Asulami, Awad Falah; Alayli, Ibrahim Abdullah; Alsulami, Khalaf Falah; Alkhairi, Faisal Ali; Alsulami, Fahad Falah; Alzahrani, Jamaan Ali Abdullah; Alotaibi, Meteeb Ghazi; Saddig, Riyadh Hassan Ali; Namazi, Aisha Mohammed Saddig (Journal of Posthumanism, 2024)
Post-traumatic stress disorder (PTSD) is a common and debilitating mental health condition that profoundly affects individuals’ well-being and quality of life. Nurses, as frontline care providers, play a critical role in managing PTSD by delivering comprehensive care that includes assessment, treatment, and emotional support. This research paper explores the multifaceted responsibilities of nurses in PTSD management, highlighting their role in identifying symptoms, providing trauma-informed care, and collaborating within multidisciplinary teams to ensure optimal treatment outcomes. Within the framework of national efforts to enhance mental health services, the Irada Mental Health Complex stands out as a leading institution in providing integrated care for individuals with PTSD. The complex offers advanced therapeutic programs based on evidence-based practices, including trauma-focused cognitive behavioral therapy, individual and group psychotherapy, as well as rehabilitation and family support services. Nurses at the complex play an essential role through ongoing psychological assessment, close monitoring of individualized treatment plans, and providing consistent emotional support. Moreover, the complex emphasizes training its nursing staff in culturally competent and trauma-sensitive care, which significantly enhances the quality of services provided and contributes to improved clinical outcomes for patients with PTSD. This paper also examines innovative therapeutic approaches, the challenges nurses encounter in caring for patients with PTSD, and the importance of cultural competence in delivering effective mental health care. By addressing these dimensions, the paper underscores the necessity of empowering nurses through continuous education, supportive organizational structures, and policy reforms that strengthen their capacity to effectively support individuals living with PTSD